Analysis of patterns of bacteremia and 30-day mortality in patients with acute cholangitis over a 25-year period. (4th May 2021) - Tan, Ming; Jensen, Thøger Gorm; Nielsen, Stig Lønberg; Schaffalitzky de Muckadell, Ove B.; Laursen, Stig Borbjerg
Abstract: Introduction: Acute cholangitis (AC) is a condition of bacterial infection in the biliary tract with a high mortality rate of around 10%. Direct association between presence of bacteremia and 30-day mortality among AC patients is sparsely investigated and remains unclear. Aims and methods: Our aim was to investigate association between bacteremia and 30-day mortality among patients with AC included over a period of 25 years. All AC patients that underwent endoscopic retrograde cholangiopancreatography (ERCP) at Odense University Hospital, between 1 January 1990 and 31 October 2015, were identified using a prospective ERCP database. Blood culture results from the patients along with antimicrobial resistance patterns were collected from a bacteremia research database. Results: During the study period, 775 consecutive AC patients underwent ERCP and blood cultures were collected from 528 patients. Among these patients 48% ( n = 260) had bacteremia. Overall, 30-day mortality in patients with blood cultures performed was 13% ( n = 69). In patients with bacteremia, 30-day mortality was 19% ( n = 49), compared to 7% ( n = 20) in patients without bacteremia ( p < .01). Presence of bacteremia was associated with increased 30-day mortality (OR [95% CI]: 3.43 [1.92–6.13]; p < .01) following adjustment for confounding factors. Among the species, bacteremia with Enterobacter cloacae was significantly associated with increased 30-day mortality (OR [95% CI]: 2.97 [1.16–7.62]; p = .02). Conclusion: Our results indicate that presence of bacteremia was associated with a nearly fourfold increase in 30-day mortality among AC patients.